Experimental assessment of determining the average size of speckles - Roman N. Sergeev (Вестник Самарского университета: Естественнонаучная серия)
The paper proposes a method for estimating the average speckle size using experimentally recorded images of speckle fields on a CMOS matrix. This method can be useful when used in speckle interferometry methods when determining their metrological parameters.